Intervention to reduce benzodiazepine prescriptions in primary care, study protocol of a hybrid type 1 cluster randomised controlled trial: the BENZORED study. Issue 1 (30th January 2019) - Vicens, Caterina; Leiva, Alfonso; Bejarano, Ferran; Sempere, Ermengol; Rodríguez-Rincón, Raquel María; Fiol, Francisca; Mengual, Marta; Ajenjo, Asunción; Do Pazo, Fernando; Mateu, Catalina; Folch, Silvia; Alegret, Santiago; et al.
Abstract : Introduction: Benzodiazepines (BZDs) are mainly used to treat anxiety and sleep disorders, and are often prescribed for long durations, even though prescription guidelines recommend short-term use due to the risk of dependence, cognitive impairment, and falls and fractures. Education of general practitioners (GPs) regarding the prescription of BZDs may reduce the overuse and of these drugs. The aims of this study are to analyse the effectiveness of an intervention targeted to GPs to reduce BZD prescription and evaluate the implementation process. Methods and analysis: The healthcare centres in three regions of Spain (Balearic Islands, Catalonia and Community of Valencia) will be randomly allocated to receive a multifactorial intervention or usual care (control). GPs in the intervention group will receive a 2-hour workshop about best-practice regarding BZD prescription and BZD deprescribing, monthly feedback about their BZD prescribing practices and access to a support web page. Outcome measures for each GP are the defined daily dosage per 1000 inhabitants per day and the proportion of long-term BZD users at 12 months. Data will be collected from the electronic prescription database of the public health system, and will be subjected to intention-to-treat analysis. Implementation will be evaluated by mixed methods following the five domains of the Consolidated Framework For Implementation Research. Ethics and dissemination: This study was approved by the Balearic Islands Ethical Committee of Clinical Research (IB3065/15), l'IDIAP Jordi Gol Ethical Committee of Clinical Research (PI 15/0148) and Valencia Primary Care Ethical Committee of Clinical Research (P16/024). The results will be submitted for publication in peer-reviewed journals. Trial registration number: ISRCTN28272199 .